The Mystery Of The Strange Bundle - Enid Blyton
Part of the "Rewards" series covering a range of Enid Blyton's work from her stories for the very young, such as the adventures of "Brer Rabbit" and "Amelia Jane", to stories for older children including the "Malory Towers" books. This book follows the adventures of the Five Find-Outers.